Agglomeration in Europe in the context of socio-ecological transition - Izabela Styczynska; Constantin Zaman (Center for Social and Economic Research (CASE), 2012)
This paper analyses the spatial distribution of economic activity in the European Union at NUTS2 level over the 2001-2010 period. The aim of the study is twofold: (i) to provide descriptive evidence of the agglomeration distribution in Europe and its evolution over time across countries; (ii) to identify the nature of agglomeration and the factors that determine its level, with particular attention paid to the socio-ecological transformation occurring in Europe. The study concludes that: a) the changes in agglomeration are sensitive to demographic transformations taking place; b) the ecological transformation has a mixed effect, depending on each country; c) significant differences are observed between new and old Member States; the crisis has had a significant influence on agglomeration but only in Western Europe.
Keywords: R11; R12; 330; spatial concentration; regional disparities; socio-ecological transformation; Ballungsraum; Agglomerationseffekt; Räumliche Verteilung; Räumliche Verteilung; Nachhaltige Entwicklung; EU-Staaten; EU-Mitgliedschaft